Inner Voice dan Self-Esteem - Christia, Mellia (UI Scholars Hub, 2007)
This study had been done to comprehend inner voice phenomena in psychopathology, especially suicide ideation in normal people. Using quantitative method, inner voice and self-esteem instruments have been developed and given to 196 students Faculty of Psychology Universitas Indonesia. The results showed that there is significant correlation between inner voice and self esteem and no sex differences in inner voice and self esteem between participants. In general, subjects inner voice state is in underestimate self-esteem, despite most of the subjects have high self-esteem.